Upaya BPRS Haji Miskin dalam Mengantisipasi Ketergantungan Pedagang Kecil Terhadap Rentenir - Asrinaldi; Vira Qutranada (El-Kahfi | Jurnal Ekonomi Islam, 2022)
This study aims to describe the perceptions of small traders towards moneylenders in Lima Kaum District and explain the efforts of PT. BPRS Haji Miskin in anticipating the dependence of small traders on loan sharks in Lima Kaum District. The type of research that the author uses is a type of field research with a qualitative descriptive approach. Data collection techniques with interviews and documentation. The data analysis technique uses the Miles and Hubemen technique, namely data reduction, data presentation, and drawing conclusions. Based on the results of the research conducted by the authors, the authors state that many traders in the sub-district of the Five People still use the services of moneylenders because the loan method is easy, fast and without collateral. Efforts made by BPRS Haji Miskin in reducing the dependence of small traders on moneylenders, namely conducting direct outreach to traders, providing education, distributing brochures to make it easier for prospective customers to find out about weekly products available at BPRS Haji Miskin and carrying out weekly financing realization, with ceilings ranging from 500,000 to 3,000,000 without collateral for 10 weeks of installments.